Increased Beta Frequency (15-30 Hz) Oscillatory Responses in Euthymic Bipolar Patients Under Lithium Monotherapy - Tan, Devran; Özerdem, Ayşegül; Güntekin, Bahar; Atagün, Murat İlhan; Tülay, Elif; Karadağ, Figen; BAŞAR, EROL (Sage Publications Inc, 2455 Teller Rd, Thousand Oaks, Ca 91320 USA, 2016)
The effect of lithium on neurocognition is not still fully explored. Brain oscillatory activity is altered in bipolar disorder. We aimed to assess the oscillatory responses of euthymic bipolar patients and how they are affected by lithium monotherapy. Event-related oscillations in response to visual target stimulus during an oddball paradigm in 16 euthymic drug-free and 13 euthymic lithium-treated bipolar patients were compared with 16 healthy controls. The maximum peak-to-peak amplitudes were measured for each subject's averaged beta (15-30 Hz) responses in the 0- to 300-ms time window over frontal (F3, Fz, F4), central (C3, Cz, C4), temporal (T7, T8), temporo-parietal (TP7, TP8), parietal (P3, Pz, P4), and occipital (O1, Oz, O2) areas. Patients under lithium monotherapy had significantly higher beta responses to visual target stimuli than healthy controls (P = .017) and drug-free patients (P = .015). The increase in beta response was observed at all electrode locations, however, the difference was statistically significant for the left (T7; P = .016) and right (T8; P = .031) temporal beta responses. Increased beta responses in drug-free patients and further significant increase in lithium-treated patients may be indicative of a core pathophysiological process of bipolar disorder and how it is affected by lithium. Whether the finding corresponds to lithium's corrective effect on the underlying pathology or to its neurocognitive side effect remains to be further explored. In either case, the finding is a sign that the oscillatory activity may be useful in tracking medication effect in bipolar disorder.
Keywords: bipolar disorder; euthymia; lithium; brain oscillations; beta response; Event-Related Potentials; Quality-of-Life; Affective-Disorder; Neuropsychological Performance; Cognitive Performance; Unaffected Relatives; Volume Increase; Functional Mri; Auditory P300; Manic Episode